The EU's new energy and climate policy framework for 2030: Implications for the German energy transition - Severin Fischer (Stiftung Wissenschaft und Politik (SWP), 2014)
In October 2014, the leaders of the 28 EU Member States in the European Council agreed upon the outline of a common strategy for energy and climate policy to 2030. Until the very end of negotiations, the agreement was subject to Poland's consent. The strategy includes quantified targets for the EU in three areas: emissions mitigation, renewable energy, and energy efficiency. At the same time, the European Council emphasized the role of national strategies in energy policy and made decisions on climate policy conditional to intergovernmental agreement. In addition, the summit extended extensive financial transfers to and exemptions for Central and Eastern European Member States. This new EU framework poses challenges for Germany's "Energiewende", the objectives of which will find considerably less support in the structures of the EU's energy and climate policy. (SWP Comments)
Keywords: 320